Features of Celiac Disease in children and adolescents with Down syndrome: a single-center experience of annual screening - Lattuada, Martina; Rebora, Paola; Fossati, Chiara; Lazzerotti, Alessandra; Paolini, Lucia; Cattoni, Alessandro; Panceri, Roberto; Valsecchi, Maria Grazia; Biondi, Andrea; Zuin, Giovanna (Frontiers in Pediatrics, 2025)
IntroductionCoeliac disease (CD) manifests more frequently in individuals with Down syndrome (DS) and its prevalence varies across different studies. This study aims to assess the prevalence of CD in children with DS and to describe their clinical, serological, and histological features. A secondary aim was to analyze the time needed for the normalization of anti-transglutaminase IgA (TGA-IgA) and anti-endomysium IgA (EMA-IgA) levels in DS compared to non-syndromic (NS) children.Materials and methodsThis retrospective monocentric cohort study included patients with DS under 18 years of age, diagnosed with CD between 2005 and 2022. Each DS patient was matched for year of birth and sex with two NS celiac children. Follow-up was 6-, 12- and 24-months post-diagnosis.ResultsThe prevalence of CD in 770 children with DS was 7.5% (95% CI: 5.8%–9.6%). 57 children with CD and DS were compared with 114 CD NS matched controls (total sample size = 171). DS demonstrated less symptoms than 114 NS CD children (26% vs. 79%, P < 0.001). In the CD DS group 81% had anti-TGA levels 10 times higher the upper limit of normal, compared to 72% in the control group. Among patients with CD and DS, 93% had histological damage equal to 3rd grade of Marsh-Oberhuber classification at diagnosis. The velocity of normalization of anti-TGA was higher in patients without DS (P = 0.005).DiscussionThis study reinforces the higher prevalence of CD in DS, emphasizing the necessity for routine screening, even in asymptomatic individuals. Despite less symptomatic presentation, patients with DS exhibited elevated antibody levels and severe histological damage. Clinicians should expect a prolonged time for antibody normalization following gluten-free diet in DS, mirroring potential challenges in diet adherence and altered immune responses.